Answer:
10,10
Step-by-step explanation:
you got this
9)1= one 1/9 for each
so do that 5 more times and u get 6/9 for each friend
or 2/3
Answer:
Step-by-step explanation:
Good evening ,
_______________
a) p(rat)=1-(0,35+0,4+0,1)
b) p(cat ∪ hamster)=0,35+0,1
c) p(dog then dog)= (0,4)²
:)
Answer:
see explanation
Step-by-step explanation:
The Remainder theorem states that if f(x) is divided by (x - h) then
f(h) is the remainder, thus
division by (x - 1) then h = 1
f(1) = 4(1)³ - 7(1)² - 2(1) + 6
= 4 - 7 - 2 + 6 = 1 ← remainder
The factor theorem states that if (x - h) is a factor of f(x), then f(h) = 0
Here f(1) = 1
Hence (x - 1) is not a factor of f(x)